(3TQM GdebJQM aj GdeUWdMs - (3CHh efUhQ eMeO GdHQhis; (3Jbj GdOjf eXaQ Hf CHj GdYR GdTGaYjs
(3ChdgG (B:s
(3CeG HYO MeO Gddg eDjO GdOjf abO QZHJ Edi LeGYI ef GdWdHI GdeJMPbjf ai TQM GdcJGH GdehShe HGdebJQM ai GdeUWdM ddEeGe CHj efUhQ eMeO GdHQhi Gdaf GdChd ai EKHGJ GdMce s
(3BNQgG (B:s
(3GdLhGH YfgG JYXjekG HbOQgG hJbQjH GdebUhO agPg eUGdM TJi hGddg GdeSJYGf hYdjg GdEJcGd Je GdcJGH GdehShe HTQM GdebJQM ai GdeUWdM s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1793s
Keywords: (3GdMOjK h GdeUWdMs